2023
DOI: 10.1371/journal.pone.0280131
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of emotion dysregulation as a core symptom of adult ADHD: A systematic review

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is a developmental disorder, with an onset in childhood, that accompanies the person throughout their life, with prevalence between 3 and 5% in adults. Recent studies point towards a fourth core symptom of the disorder related to the emotional information processing that would explain the repercussions that ADHD has on the social, academic, and professional life of the people affected. This review aims to describe emotion dysregulation features as well as the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…This observation aligns with previous literature indicating a link between ADHD and emotional dysregulation. 31 The heightened emotional dysregulation in anxiety-related disorders aligns with the well-established connection between anxiety and emotional reactivity. 32,33 Similarly, individuals with compulsive sexual behavior disorder demonstrate distinctive patterns of emotional dysregulation.…”
Section: Discussionmentioning
confidence: 81%
“…This observation aligns with previous literature indicating a link between ADHD and emotional dysregulation. 31 The heightened emotional dysregulation in anxiety-related disorders aligns with the well-established connection between anxiety and emotional reactivity. 32,33 Similarly, individuals with compulsive sexual behavior disorder demonstrate distinctive patterns of emotional dysregulation.…”
Section: Discussionmentioning
confidence: 81%
“…Attention-deficit hyperactivity disorder (ADHD) is a valid and recognized neurodevelopmental disorder affecting around 2.8% of the adult population ( 106 ) and is characterized by hyperactive-impulsive and/or inattentive symptoms with onset in childhood, before 12 years old ( 7 ). ED is considered as a central symptom of adult ADHD ( 25 , 107 ), and several authors have emphasized its central role in externalizing behaviors and functional impairment in social and professional spheres ( 8 , 25 , 107 ). When looking at ED triggers in adult ADHD, we believe – as suggested by some authors ( 25 ) - that impatience and boredom are the most relevant one, especially in patients with hyperactivity, even though this aspect has not specifically been studied to our knowledge.…”
Section: Emotion Dysregulation Triggers and Interpersonal Stylementioning
confidence: 99%
“…Interestingly, recent genome-wide association studies (GWAS) demonstrated that ED should not be considered a mere comorbidity of ADHD, being associated per se with genetic liability for the disorder (293). In view of these and similar findings, it has been proposed that ED is a core aspect of ADHD (284,294,295) and that ADHD should be included among the EDD (5). Some authors also suggest that ED should be seen as the fourth dimension of ADHD and integrated into its diagnostic criteria (285,296,297).…”
Section: Emotional Dysregulation Is a Core Feature Of Adhd With Cruci...mentioning
confidence: 99%